Forming the subterranean space by means of a new tool (geohod) - Efremenkov А. В. Andrey Borisovich (2011, 2011)
The article provides the main fundamental distinctions of geohod operation and its place in the general classification of mining machines. A complex of necessary works for designing basic elements and systems of geohod has been defined. The article grounds the necessity of developing a new scientific field - geodynamics of subterranean machines.